Faktor Kunci Keberlanjutan Organisasi Nirlaba di Bali - Kadek Wahyuni Andhityawati; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2022)
The COVID-19 pandemic that has lasted since 2019 until now has created an uncertainty for every individual and organization around the world with an emphasis on the very strong economic impact that has led to a global recession. Uncertainty has placed nonprofits in an increasingly competitive environment. The importance of the existence of nonprofits requires that the organization needs to ensure its sustainability through proper planning and implementation of strategies. This study uses a qualitative approach. Interviews and observations were conducted to collect the data. Data reduction and coding was done to analyse all findings. Key factors influencing the sustainability include the existence of financial management in accordance with non-profit best practices; diversity of funding sources; good and well-maintained relationship management with donors; beneficiaries involvement thoroughout the project, the existence of wide and diverse partnerships and networks; the existence of advocacy efforts; the existence of vision, mission, and organizational values that are understood by all parties involved, leadership factors that are in accordance with organization character; the existence of project management; creative and innovative organizational marketing factors. A deep and thorough understanding of all these key factors will support the organization's ability to develop its sustainability strategy during this pandemic.